Avaliação mutagênica em cirurgiões dentistas expostos ocupacionalmente à Radiação Ionizante - Mesquita, Maria do Amparo da Silva Bida (2011)
X-rays are widely used in medical and dental practices, but are potent mutagens able to induce mutations and chromosomal aberrations. This study aimed to evaluate the effects of ionizing radiation-induced X-rays in exfoliated buccal mucosa cells of dentists exposed occupationally, through the application of the micronucleus test, to show the number and frequency of micronuclei, and other nuclear abnormalities such as binucleated cells, karyorrhexis (nuclear fragmentation) and karyolysis (nuclear dissolution). The age of the study population was 32 to 65 years, represented by dentists and 95% white and 5% were black, while the unexposed was 30% white and 25% were black. In relation to exposure to chemical and physical agents, the results showed that 100% of dentists are exposed to both types of agents. Over the past decade, 65% of those exposed and 45% of unexposed X-ray performed for therapeutic purposes. The working time, the group of subjects with exposure to ionizing radiation overcomes the unexposed group, 19.40 ± 8.74 vs corresponding 11 to 32 years in expoxtos and 6.55 ± 7.09 vs corresponding 11 to 25 years in the unexposed. Regarding the use of protection of 100% in both groups did not use protection. The assessment of mutagenicity was observed by the number of micronuclei in exfoliated cells of oral epithelium, vs. 5.85 ± 3.58 in those exposed and 1.00 ± 0.85 in the unexposed, but also by the frequency of micronuclei, and 0.41 ± 0.27 MN in the exposed and 0.02 ± 0.04 MN in unexposed, with a significance of p <0.001 in exposed compared to unexposed. Abnormalities such as nuclear karyorrhexis (39.49 ± 16, 29 vs 16, 03 ± 8.61), karyolysis (6.92 ± 5.87 x 1.11 ± 0.99) and binucleated cells (12.45 ± 8 , 43 x 0.76 ± 0.23) compared to unexposed, demonstrate apoptosis, necrosis and citotocixidade and were statistically significant p <0.01. No correlation was found between positive lifestyle habits, genetic diseases and the presence of micronuclei and nuclear abnormalities. Thus, the results of this study indicate that dental radiation induced damage to the genetic material of cells exfoliated buccal mucosa, also causing increased apoptosis, indicating that the use of this procedure should be ordered only when necessary. This work also demonstrates the importance of evaluating the nuclear and other abnormalities not only micronuclei as indicators of DNA damage. Concern about these effects is relevant mainly to the occupationally exposed, as well as establishing a prognosis of the incidence of cancer development, the monitoring of exposure of dentists to these agents can be an important step for planning strategies and security measures.